Penerapan Internet of Things Untuk Pemantauan Kondisi Tanaman Dengan Wireless Sensor Network - Anggra Triawan; Ali Mufti Syaefudin (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2022)
Conditions in plants that lack or excess sunlight causes plants to wither quickly, it is feared that it will harm the community, Less accurate in assessing conditions around plants and less effective in uniting ornamental plants when outdoors are factors that are factors in the development of technology that supports various types of plants. type of plant. technology, this research aims to create a prototype with the Internet Of Things model which is the concept of connecting sensors to the internet that can create an open connection. a prototype system was created to effectively integrate ornamental plant conditions to treat plants and obtain more accurate plant condition data. By using the Prototype method to make systems and tools using a DHT22 sensor for temperature and humidity data, a Soil Moisture sensor for soil moisture, an ultrasonic sensor HC-SR04 to be able to see the condition of the water tank, and NodeMCU as a microcontroller that receives data from the sensor and will be sent. to Cloud Storage via the internet using Wireless Sensor Network technology. The results of the calculation of the accuracy of the temperature measuring instrument were tested by comparing DHT-22 with a mercury thermometer with an average of "0.82%". The test results show the results of "90%" for the expert test and "88.29%" for the user test. expected and can help the community in unifying the condition of ornamental plants to be more effective and provide accurate information.